A comprehensive peri-operative protocol to decrease the risk of infection post coccygectomy: a case series study - Mohannad W. Awwad; Rohail Mumtaz; Omar Al Sultan; Musab Al Ageel; Waleed Awwad (BMC Musculoskeletal Disorders)
Abstract Background Coccygectomy is the definitive treatment of coccygodynia refractory to conservative therapy, but post operative wound infection poses a significant challenge in these patients. We introduce a novel peri-operative technique incorporating a specific pre-operatively dietary regimen, polyethylene glycol enema, and prophylactic antibiotics. Post-operatively, patients adhered to strict hygienic protocols in addition to receiving antibiotics. This technique successfully reduced the incidence of surgical site infection post coccygectomy to a rate of 0.0%. Methods A retrospective review was conducted on 21 patients who underwent partial or complete coccygectomy for coccygodynia refractory to 6 months of conservative therapy. Patients were treated using our novel protocol to minimize the infection risk and significant improvement in their pain. Results All of the patients experienced uneventful post operative recovery except for 1 solitary case of delayed wound healing. This case was treated with a silver impregnated dressing and demonstrated full wound recovery 1 week later. Additionally, pain scores showed a significant reduction of pain before and after surgery. These results highlight the efficacy of our enhanced peri-operative protocol in preventing surgical site infection as well as substantial pain relief. Conclusion Our findings are consistent with the existing literature, demonstrating that an enhanced peri-operative protocol not only effectively prevents post-operative infections but also facilitates significant pain relief in patients undergoing coccygectomy. This novel peri-operative protocol may offer a new standard for managing post-surgical outcomes in coccygectomy, though prospective studies are needed to further validate these results.